Special issue: Proceedings of the 15th ISIC - The Information Behaviour Conference, Aalborg, Denmark, August 26-29, 2024 (Information Research an international electronic journal, 2024)
‘It never seems to stop’ Six high school students’ experiences of information overload Mira Grønning Aadland, Jannica Heinström Exploring scholarly perceptions of preprint servers Shir Aviv-Reuven, Jenny Bronstein, Ariel Rosenfeld Enhancing conceptualisations of information behaviour contexts through insights from research on e-dictionaries and e-lexicography Theo JD Bothma, Ina Fourie Trends in data literacy, 2018-2023: a review of the literature Leanne Bowler, Charlie Shaw Analysis of collaborative innovation behaviour and its influencing factors in scientific research crowdsourcing platforms: based on the fsQCA method Jiajun Cao, Yuefen Wang, Xin Xie, Yuanzhi Lv, Peng Chen Information relations for social change: exploring the information behaviour of academics undertaking impact work Joann Cattlin, Lisa M. Given Collaborating, collecting and representing: queer independent archives and their connections with GLAM institutions in Aotearoa/New Zealand Alison S. Day Health information post-encountering behaviours on social media platforms Khalid U Fallatah, Morgan A Harvey, Sophie Rutter Information seeking behaviour in music conductors’ repertoire selection Christina Firkins, Michael Barrett-Berg, Ina Fourie Models and theories that can guide grief and bereavement information interventions: an information behaviour lens Ina Fourie Case study on a scientific oral history project using information practice analysis Deborah A. Garwood The reading practices of people with neuropsychiatric disabilities: a review of library and information science literature Katarina Hagberg, Karin Lundin, Anna Lundh, Åse Hedemark Representational exchange and edgework: towards theorising the coping with fragmentary information Isto Huvila Situating complexity: information behaviour in the contact zone Hye Lim Joy Nam Digital health applications and health literacy: an explorative analysis Aylin Imeri, Sabrina Schorr, Sebastian Merkel To share or not to share? Image data sharing in the social sciences and humanities Elina Late, Mette Skov, Sanna Kumpulainen Analysing humanities scholars’ data seeking behaviour patterns using Ellis' model Wenqi Li, Pengyi Zhang, Jun Wang Can ChatGPT provide health information as physicians do? Preliminary findings from a cross-sectional study of online medical consultation Siqi Luo, Hongyi Qin, Hanlin Li, Cui Huang Mapping the road ahead: understanding social factors that shape vehicle residents’ information grounds Kaitlin E. Montague An information behaviour exploration of personal and family information and curation of our life histories Bhuva Narayan, Annemarie Zijlema, Vanessa Reyes, Mary Anne Kennan Layers upon layers: data sharing & reuse challenges in archaeological contexts Michael Olsson, Olle Sköld, Lisa Andersson Development in the adoption of a national digital healthcare system and experience at taking new technology in use – changes from 2019 to 2022 Ágústa Pálsdóttir Ubiquitous but invisible – public librarians’ self-imposed professional information practices as articulation work Ola Pilerot, Jenny Lindberg Transdisciplinarity: an imperative for information behaviour research Sarah Polkinghorne, Paul Bowell, Lisa M. Given God’s intermediaries: a study into chaplains’ information behaviour Kieran Robson, Ian Ruthven, Perla Innocenti COVID-19 information spaces, boundaries, and information sharing: an interview study Togzhan Seilkhanova, Theodore Dreyfus Ledford, Jodi Schneider Information from sound: exploring sounds and listening in information practices research Owen Stewart-Robertson Information practices in multi-professional work in urban planning Anna Suorsa, Anna-Maija Multas, Emilia Rönkkö, Eevi Juuti, Anelma Lammi, Heidi Enwald Searching for people in the workplace: aims, behaviour, and challenges Tanja Svarre, Marianne Lykke, Ann Bygholm Surfacing the ‘silent foundation’: which information behaviour theories are relevant to public library reference service? Amy VanScoy, Africa S. Hands, Katarina Švab, Tanja Merčun Using progress logs to research the information behaviour of higher education students in prison Isabel Virgo Savolainen’s everyday information practices: concept and development Xinyue Wang Digital stress among Chinese adolescents: a focus group study Zhang Wen, Chen Yifan, Cao Gaohui Creating, using, and sharing embodied information in the ultrarunning community on Instagram Laura Williams, Andrew Cox, Andrea Jimenez Isolated, individualised, and immobilised: information behaviour in the context of academic casualisation Rebekah Willson, Owen Stewart-Robertson, Heidi Julien, Lisa M. Given Contextual information needs of people in life transitions struggling with obsessive-compulsive disorder Dawei Wu, Yuxiang Chris Zhao, Yan Zhang, Shijie Song Engaging with AI painting: exploring motivations and challenges in laypeople's creative information practices Xiaoyu Zhang, Sicheng Zhu, Yuxiang Chris Zhao, Mingxia Jia, Qinghua Zhu Examining information needs of public data service users: a study based on the ‘Message Board for Leaders of People’s Daily in China’ Xiaoyue Zhang, Jinya Liu, Xinyue Wang, Wanteng Ma, Pu Yan